2015
DOI: 10.1016/j.redee.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of strategic human resource practices on knowledge management and firm performance

Abstract: información del artículo Historia del artículo: Recibido el 7 de abril de 2014 Aceptado el 17 de marzo de 2015 On-line el xxx Códigos JEL: D830 L250 M500Palabras clave: Gestión del conocimiento Prácticas estratégicas de recursos humanos Resultados de la empresa r e s u m e n La evidencia empírica previa señala que tanto la gestión del conocimiento como las prácticas de recursos humanos pueden interactuar de diversas formas para mejorar los resultados de la empresa. Partiendo de esta idea, el objetivo de este t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 80 publications
(148 reference statements)
3
45
0
3
Order By: Relevance
“…Further, it is possible to obtain the necessary resources for new technology adoption and technology improvement [51]. Capital acts like a precursor to organizational innovation and performance [52]. Previous studies focusing on the impact of transformational leadership have predominantly studied human capital rather than social capital [53,54].…”
Section: Moderating Effects: Social Capitalmentioning
confidence: 99%
“…Further, it is possible to obtain the necessary resources for new technology adoption and technology improvement [51]. Capital acts like a precursor to organizational innovation and performance [52]. Previous studies focusing on the impact of transformational leadership have predominantly studied human capital rather than social capital [53,54].…”
Section: Moderating Effects: Social Capitalmentioning
confidence: 99%
“…By means of propaganda, recruitment, hunting and employment, human resources concentrate resources and choose suitable jobs. Through a series of pre job training, human resources are gradually adapted to the needs of enterprise positions, creating value for enterprises and meeting the development needs of enterprises [3]. Human resources management also includes follow-up personnel services, personnel benefits and even the operation of personnel leaving the related procedures.…”
Section: Human Resource Managementmentioning
confidence: 99%
“…competitors, academic institutions, consulting firms, and industry associations), and the integration of both sources plays vital role for organizational effectiveness (Choi, Poon, & Davis, 2008). Moreover, organizations that constantly owns, acquire and manage updated knowledge through proper 'KM' strategy may sustain a superior position among competitors (Sanchez et al, 2015). Previous studies have confirmed that 'KM' has a positive association with organizational performance, innovation and competitiveness (for example, Chadee & Raman, 2012;Hsiao, Chen, & Chang 2011).…”
Section: External-knowledge Management (E-km)mentioning
confidence: 99%
“…However, specific to the effect of external sources of knowledge in 'MI' seems underdeveloped in emerging economies (Chadee & Raman, 2012) like china. As, both tacit and explicit knowledge if managed through proper strategy, may become a key resource of competitive advantage (Sanchez, Marin, & Morales, 2015). Moreover, knowledge related to profitability and competitiveness inside and outside the organization is of being imperfectly known (Zhao et al, 2012).…”
Section: External-knowledge Management (E-km)mentioning
confidence: 99%